Pengungkapan ESG dan Kinerja Perusahaan: Keunggulan Kompetitif sebagai Moderasi - Fauziyah Syifa Nurlaila; Siti Mutmainah (Jurnal Proaksi, 2025)
Main Purpose – This study aims to analyze the effect of ESG diclosure on firm performance with competitive advantage as a moderating variable. Method – The sample selected using purposive sampling from the financial industry listed on the Indonesian Stock Exchange (IDX) for the period 2021-2023. The analysis technique employed is panel data regression using E-Views. Main Findings – Theresult indicate thet ESG disclosure has a positive and significant effect on firm performance. However, competitive advantage does not moderate the relationship between ESG disclosure and frim performance. Theory and Practical Implications – These implications reinforce the importance of integrating ESG into business strategies to enhance competitiveness and create long-term value. Novelty – This study provide a perspective on the role of competitive advantage as a moderating variable in the relationship between ESG disclosure and corporate performance in the financial industry.